A Study of Load Balancing Techniques in Cloud - Poulose, Martina; Azath, M (International Journal of Computer Sciences and Engineering, 2015)
Cloud computing is a promising computing paradigm. Load balancing and rebalancing in cloud are important and challenging research area. Distributed file systems is the main building block in cloud computing. The large files will be divided into number of chunks and distributed into different systems. These chunks were allocated to each node to perform map reduce functions parallel over the nodes. Cloud is a dynamic environment, updating, replacing and adding of new nodes to the environment is a normal concern. This will impact the anatomy of the system and the chunk distribution will become uneven among the nodes. To overcome this, reallocate the chunks uniformly in the nodes. Load balancing and re-balancing helps to achieve high user satisfaction and well resource utilization. Emerging distributed systems are strongly depends on a central node for chunk reallocation. In a giant cloud central load balancer is put under significant workload and may lead to a performance bottleneck and single point of failure. This survey aims to study the different algorithms and issues of load balancing in cloud computing.